2015
DOI: 10.1016/j.breast.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemotherapy is not a contraindication for nipple sparing mastectomy

Abstract: NSM after NCH is not associated with a statistically significant difference in terms of post-operative complications, total nipple loss for necrosis or margins, and results improve with experience. The loco-regional relapse rate was higher after NCH, yet it was consistent with traditional mastectomy in the high-risk setting. There is no need to avoid NSM after NCH for locally advanced cancers, if the retro-areolar margins of resection are clear at the time of surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 29 publications
0
36
0
1
Order By: Relevance
“…For example, some groups are performing NSM when the tumor is less than 2 cm from NAC. [14]. The same group and others [15] are also performing NSM in selected patients after neoadjuvant chemotherapy.…”
Section: Oncological Safetymentioning
confidence: 99%
“…For example, some groups are performing NSM when the tumor is less than 2 cm from NAC. [14]. The same group and others [15] are also performing NSM in selected patients after neoadjuvant chemotherapy.…”
Section: Oncological Safetymentioning
confidence: 99%
“…This in turn had improvement in patient satisfaction and psychosexual benefit. The NSM is a safe surgical procedure even in patients undergoing neo-adjuvant chemotherapy, and they are also suitable in prophylactic mastectomies in high-risk women [21, 22]. For its feasibility, it is a mandatory negative retro-areolar frozen section.…”
Section: Surgerymentioning
confidence: 99%
“…There have been a limited number of studies evaluating complication rates in patients undergoing NAC followed by SSM or NSM with IR, with conflicting results demonstrated. [21][22][23][24][25][26][27] Several studies have demonstrated no increased risk in patients having immediate reconstruction following NAC. 21,[24][25][26][27] On the other hand, others have reported very high complication rates in this setting.…”
Section: Rates Of Lrr In Patients With Smaller Tumors Have Been Repormentioning
confidence: 99%